Living La Vita Apostolica: Longevity of Nuns in Late-Medieval Holland - Zuijderduijn, Jaco (Age, Culture, Humanities: An Interdisciplinary Journal, 2025)
We know little about the odds of growing old in the later Middle Ages because reconstructions of the longevity and life expectancy of populations require baptismal, marriage, and death registers, which only gradually appear after 1500. The few earlier reconstructions that are available concern males; the female experience of ageing is mostly based on small samples of elite women who lived in the Middle Ages. This paper discusses a necrology of a nunnery in late medieval Holland that provides data on the lives of religious women, from novitiate until death. It allows for a reconstruction of vital events, most notably longevity and life expectancy, and of mortality in late medieval Holland.